2019
DOI: 10.1101/512202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined Transcriptomics and Proteomics Forecast Analysis for Potential Genes Regulating the Columbian Plumage Color in Chickens

Abstract: 31Background 32 Coloration is one of the most recognizable characteristics in chickens, and clarifying 33 the coloration mechanisms will help us understand feather color formation. "Yufen I" 34 is an commercial egg-laying chicken breed in China, that was developed by a 35 three-line cross using lines H, N and D. Columbian plumage is a typical feather 36 character of the "Yufen I" H line. To elucidate the molecular mechanism underlying 37 pigmentation of Columbian plumage, this study utilizes the technology … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In previous studies, omics data were used to explore feather colour formation-related genes. The formation of Columbian plumage in chickens was related to changes in the expression of MED23 , FZD10 , WNT7B and WNT11 21 . DEGs between black and white feather colours in ducks were enriched in the pathways of melanogenesis ( c-Ki t/ TYR / TYRP1 ) and tyrosine metabolism ( TYR / TYRP1 ) 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, omics data were used to explore feather colour formation-related genes. The formation of Columbian plumage in chickens was related to changes in the expression of MED23 , FZD10 , WNT7B and WNT11 21 . DEGs between black and white feather colours in ducks were enriched in the pathways of melanogenesis ( c-Ki t/ TYR / TYRP1 ) and tyrosine metabolism ( TYR / TYRP1 ) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The formation of plumage colour is also influenced by the expression of various genes related to pigment formation in feather follicles during the growth period 16 . As the pivotal position for feather formation and melanogenesis, transcriptome profiling of the feather follicle has been performed to elucidate the process of morphogenesis and to identify candidate genes of diverse feather shapes and colours [17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…The study revealed co‐differential expression of 170 genes/proteins, with 122 genes/proteins displaying the same expression trends in both transcriptome and proteome profiles. The low to moderate correlation could be attributed to a variety of factors, including translation efficiency, alternative splicing, mRNA stability, folding, assembly, transport and localization, secretion, and degradation ( 48 – 50 ). Since the present study utilized publicly available transcriptomics databases and proteomics results from the current assessment, this 122 co-differentially expressed genes/proteins might be considered as representative of altered biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome profiling have shown that feathers from different parts of the body, characterized by different forms and serving different functions, undergo different genetic bases during generation at embryonic stages or regeneration thereafter [ 34 , 35 , 36 ], thus comparison between the black skin and other skin regions could help infer function of differentially expressed genes. Proteomic profiling could provide further evidences of the genetic differences underlying formation of different feathers [ 37 ]. On the other hand, the transcriptomic comparison of other skins between breeding and non-breeding season could reduce the difference caused by other physiological changes, instead of production of the black substance, which increase the causality of research results.…”
Section: Discussionmentioning
confidence: 99%